Analisis Kepuasan Konsumen terhadap Loyalitas Konsumen dengan Dimoderasi oleh Faktor Harga dan Variasi Produk Makanan Sehat pada PT Melia Sehat Sejahtera - Amrin Mulia Utama Nasution (Mahesa Research Center, 2023)
Many providers in Indonesia currently have many products such as PT Melia Sehat Sejahtera. The success of product development has made PT Melia Sehat Sejahtera a well-known in Indonesia. The many awards this has won has made PT Melia Sehat Sejahtera always be number one thanks to the level of customer loyalty. Consumer loyalty according to behavioral understanding is consistent with repurchasing behavior as well as a measure of customer preference to repurchase and the tendency to switch to the product. Repurchase intention is strongly influenced by consumer satisfaction with a product. However, there are two studies which state that it has a negative effect on consumer loyalty, so that a moderating variable appears. This research was tested on 133 respondents who then collected the data and tested its feasibility. After the feasibility test, a data analysis test was carried out using SEM (regression) with the help of the SmartPLS program. This study resulted in the following conclusions 1) The strong role of consumer satisfaction (93%) on consumer loyalty at PT Melia Sehat Sejahtera, because PT Melia Sehat Sejahtera is a highly recommended place to eat with its food choices, PT Melia Sehat Sejahtera is also easy to get, with many branches in each region make it easier for consumers to buy PT Melia Sehat Sejahtera products. 2) Consumer satisfaction which is moderated by the price of PT Melia Sehat Sejahtera's products has a relatively small effect (1%) on consumer loyalty and price can also play a direct negative role (-1.3%) on consumer loyalty. This is because the price is competitive compared to similar products. 3) The role of the relatively small level of consumer satisfaction (8%) is moderated by product variations on consumer loyalty at PT Melia Sehat Sejahtera and product variety can play a direct role on consumer loyalty by (5%). This is due to the lack of variety of PT Melia Sehat Sejahtera's products.